Luteinising hormone profiles in conception and non-conception natural cycles. (4th March 2019) - Johnson, Sarah; Schiffner, Julia; Freundl, Guenter; Bachmann, Nina; Gnoth, Christian
Abstract: Objective: The aim of this study was to assess whether luteinising hormone (LH) surge characteristics influenced the likelihood of conceiving naturally. Methods: This was a single-cycle, home-based, observational, case-controlled study. Volunteers collected daily urine samples for one menstrual cycle. LH was measured and the basal levels, surge day, peak day, peak concentration and magnitude of LH surges were examined. Predictive models using sociodemographic data, LH surge characteristics, and sociodemographic data combined with LH profile properties, were evaluated. Results: The surge profile did not differ between cycles with early or late ovulation and was not affected by age or body mass index (BMI). The mean LH surge day was day 16 for both groups. Mean LH surge and concentrations did not differ between groups (surge concentration 54.8 IU/l vs. 58.2 IU/l and peak concentration 82.0 IU/l vs . 81.6 IU/l for pregnant vs . non-pregnant volunteers, respectively). Non-pregnant volunteers were more likely, however, to have a raised or a reduced basal LH on day 6 or have an atypical LH profile. Sociodemographic characteristics were significant predictors of pregnancy, and sociodemographic variable-based models had the greatest predictive ability for conception, providing up to 65% predictive accuracy. Conclusions: Sociodemographic variables can be used to predict the likelihood of a woman conceiving naturally. Provided an LH surge is present, its profile does not relate to the likelihood of spontaneous pregnancy. The conception rate was significantly lower, however, in women with elevated or reduced basal levels of LH, suggesting that follicular maturation needs an optimal basal level of LH in natural conception cycles. Trial registration: ClinicalTrials.gov identifier: NCT01577147.